THE EFFECT OF TUBEROINFUNDIBULAR DOPAMINERGIC-NEURONS ON PROLACTIN AND ALPHA-MELANOCYTE STIMULATING HORMONE-RELEASE - Bedrandecastro, J. C.; Petrovic, S. L.; Khorram, O.; Mccann, S. M. (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
The effect of tubero-infundibular dopaminergic neurons (TIDA) on the release of prolactin (PRL) and alpha-melanocyte stimulating hormone (alpha-MSH) was studied in median eminence-lesioned (MEL) male rats (N = 6-28). Plasma PRL and alpha-MSH levels were significantly elevated 2 (86.1 +/- 19.8 and 505.1 +/- 19.1 ng/ml), 4 (278.7 +/- 15.5 and 487.4 +/- 125.1 ng/ml), 7 (116.2 +/- 16.2 and 495.8 +/- 62.6 ng/ml) and 14 (247.3 +/- 26.1 and 448.4 +/- 63.8 ng/ml) days after MEL when compared to sham-operated control animals (55.5 +/- 13.4 and 56.2 +/- 6.1 ng/ml, respectively). MEL altered plasma PRL and alpha-MSH levels in a differential manner, with a 1.5-to 5.0-fold increase in PRL and an 8.0-to 9.0-fold increase in alpha-MSH. The increase of alpha-MSH levels occurred abruptly and remained constant from days 2 to 14. These observations indicate that TIDA plays an important role in the pituitary release of PRL and alpha-MSH and provide evidence that the release of the two hormones occurs in a differential manner.
Keywords: PROLACTIN; ALPHA-MELANOCYTE STIMULATING HORMONE; TUBEROINFUNDIBULAR DOPAMINERGIC NEURONS; MEDIAN EMINENCE; PITUITARY